Method of deflection corrected tonometry with phantom vessel experiments. (January 2019) - Drzewiecki, G.; Krishna, G.; Katta, H.
Abstract: Background: The Continuous Non-Invasive measurement of arterial Blood Pressure [CNIBP] is possible via the method of arterial tonometry and the arterial volume clamp methods. Arterial tonometry successfully measures continuous arterial pressure but requires large vessel deformation and a highly miniaturized pressure sensor to obtain a direct calibration of pressure. A properly designed tonometer is capable of achieving pressure accuracy of less than 5% error at the radial artery. The volume clamp method achieves comparable errors but is generally restricted to the very peripheral arteries. Since the brachial or radial arteries are preferable sites to record blood pressure, tonometry is generally preferred. However, due to its strict operating requirements, tonometry requires a highly skilled operator. The greatest source of measurement error results from slight deviation from the artery wall applanation position. In this study, a method for correcting tonometry deflection error is introduced and evaluated using preliminary experiments. Methods-modeling: In prior analysis it has been shown that arterial wall flattening causes contact stress to become uniform and equal to the arterial pressure. In this article, we derive the contact stress for deflections other than the ideal applanation position and to allow variable vessel deflection. This analysis permits the contact stress to be corrected for tonometer positions that are not exact so that pressure accuracy is maintained in spite of less than ideal positioning. This will alleviate the necessity for highly skilled users and allow rapid determination of the pulse pressure. Methods-experimental: Experiments were performed to evaluate applied model corrections for tonometer accuracy versus vessel deflection. Two experiments were performed to evaluate tonometer accuracy when deflection is varied. The first experiment used no deflection correction and the second experiment applied model derived deflection correction. A force sensor was used to deflect a phantom latex vessel of known internal pressure. The corrected contact pressure was then compared with known pressures to evaluate the pressure accuracy. Results-modeling: a geometric model was derived for vessel contact area versus deflection. This resulted in a formula that provides contact area continuously for any amount of deflection. Once the contact area is known the average tonometer contact pressure was obtained that corresponds with the vessel internal pressure. Results – experimental: A latex tubing phantom vessel was pressurized to a known amount and was deflected in increments over its full diameter while measuring contact force at each position. The model-derived formula was then used to calculate pressure at each position. The calculated pressure was then compared with known internal pressure to evaluate pressure accuracy for all the phantom pressure and deflection points. Conclusions: A modeling method for tonometer deflection correction was derived and evaluated using a phantom vessel. Average error was significantly reduced over the non-corrected data. The variability of error was also reduced for all data points collected. The experiments reveal that blood pressure measurement error can be reduced to levels obtained in near ideal tonometry conditions without the need for precise position control. The relaxed user precision is anticipated to simplify the use and design requirements for arterial tonometry in practice. Highlights: A deformation model of Arterial Tonometry geometry was derived. A Model-based method corrects for deformation error in Arterial tonometry. Deflection-corrected tonometry was evaluated using a Phantom Artery. Data confirmed deflection correction model restores tonometer accuracy.